SIMULASI PERBAIKAN LEAD TIME PROSES PRODUK BUMPER MENGGUNAKAN VALUE STREAM MAPPING DAN PROMODEL DI PT. SUZUKI INDOMOBIL MOTOR - Ismail Kurnia; Dionisius Debata; Prima Fithri (Sekolah Tinggi Teknologi Industri Padang, 2022)
The development of the industry in this globalization era is very rapid, causing complex problems. The era of globalization requires all aspects of life to adapt to the development of more advanced times with the sophistication of its technology. One of the ways to increase excellence is to minimize waste in the production line. Beginning by describing the actual condition of the production line and trying to eliminate the waste in order to realize a lean value stream. The method used is a value stream mapping that is useful for seeing the processing time detail so that it knows the value added and non value added as well and Promodel software to simulate the proposed improvement given to improve the process lead time. Based on the current stream map that has been made known waste activities that occur is over process, inventory, and waiting. The front bumper assy panel of the Model Y9J at PT. Suzuki Indomobil Motor is the product with the highest demand for spare parts, where the lead time for stock is 21.2 days, and the lead time for processing is 1.14 days so it is necessary to make improvements using a Value stream mapping simulation, so stock lead time to 6.1 days and process lead time to 0.6 day.